Infants' Ability to Detect Emotional Incongruency: Deep or Shallow?. (4th January 2019) - Crivello, Cristina; Poulin‐Dubois, Diane
Abstract : Infants can detect individuals who demonstrate emotions that are incongruent with an event and are less likely to trust them. However, the nature of the mechanisms underlying this selectivity is currently subject to controversy. The objective of this study was to examine whether infants' socio‐cognitive and associative learning skills are linked to their selective trust. A total of 102 14‐month‐olds were exposed to a person who demonstrated congruent or incongruent emotional referencing (e.g., happy when looking inside an empty box), and were tested on their willingness to follow the emoter's gaze. Knowledge inference and associative learning tasks were also administered. It was hypothesized that infants would be less likely to trust the incongruent emoter and that this selectivity would be related to their associative learning skills, and not their socio‐cognitive skills. The results revealed that infants were not only able to detect the incongruent emoter, but were subsequently less likely to follow her gaze toward an object invisible to them. More importantly, infants who demonstrated superior performance on the knowledge inference task, but not the associative learning task, were better able to detect the person's emotional incongruency. These findings provide additional support for the rich interpretation of infants' selective trust.